ANALISIS DETERMINAN SOSIAL TERHADAP PREVALENSI PENYAKIT MENULAR SEKSUAL DI KALANGAN REMAJA KOTA MEDAN - SURJADI RIMBUN (LP2MTBM MAKARIOZ, 2022)
Medan City is the 3rd largest city in Indonesia, where the number of young people in Medan City in 2022 is 598366 people, where the number of young people affected by this sexually transmitted disease is 9,050 cases in 2022 which increased from 2017 of 8,997 cases. This situation is caused by a lack of understanding of sexually transmitted diseases, as well as a lack of socialization from the health office regarding sexually transmitted diseases to young people in the Medan City area, so that the low understanding and knowledge about sexual diseases will have an impact on the chaotic and indifferent attitude of the young people of Medan City, resulting in the rampant occurrence of free sex and promiscuity among them which results in many cases of infectious diseases sexual appearance. This study used descriptive analytical method. The population of this study amounted to 9,050 young people who were exposed to sexually transmitted diseases and hospitalized, where the sample taken amounted to 60 young people who were exposed to sexually transmitted diseases and hospitalized. From the results of existing research, it can be concluded that young people infected with sexually transmitted diseases are young people whose prevalence is in Medan Kota District where this situation is caused by the lack of socialization about sexually transmitted diseases by the Medan City health office, as well as incorrect understanding from young people in Medan City District regarding knowledge literacy related to sexually transmitted diseases